Debridement, antimicrobial therapy, and implant retention (DAIR) as curative strategy for acute periprosthetic hip and knee infections: a position paper of the European Bone & Joint Infection Society (EBJIS) - I. K. Sigmund; T. Ferry; R. Sousa; A. Soriano; A. Soriano; A. Soriano; W. J. Metsemakers; W. J. Metsemakers; M. Clauss; R. Trebse; M. Wouthuyzen-Bakker (Journal of Bone and Joint Infection)
It has been shown that the outcome of a DAIR (debridement, antimicrobial therapy, and implant retention) procedure depends on multiple factors (e.g. infection type, host factors, clinical presentation, condition of surrounding soft tissue, causing pathogen, surgical technique, antimicrobial therapy); therefore, adequate patient selection is key for DAIR success. In this position paper, we discuss the most relevant factors influencing the outcome and define indications, contraindications, and risk factors for a DAIR procedure based on the most robust and most recently published data. Furthermore, we discuss the surgical technique in combination with systemic antimicrobial therapy in patients undergoing a DAIR procedure.